Role of stretch therapy in comprehensive physical habilitation of patients with Charcot–Marie–Tooth hereditary neuropathy - N. A. Shnayder; S. I. Goncharova (Нервно-мышечные болезни, 2015)
Charcot–Marie–Tooth hereditary neuropathy (Charcot–Marie–Tooth disease, CMT) is the most common form of hereditary neuropathies, accompanied by sensory disorders, progressive muscle weakness with the formation of disabling contractures of the limbs. Currently, the main treatment program is effective CMT habilitation, which can prevent the development of limb deformities and thereby improve the life quality of the patient. Stretch therapy is one of the most effective methods of prevention and treatment of contractures in patients with CMT. This article provides a brief review of the literature regarding the use of stretching as physical therapy program of CMT habilitation.